Municipal solid waste landfill evaluation using fuzzy approach - Nur Syibrah Muhamad Naim (Fakulti Sains dan Teknologi, 2012)
The issue of landfilling is often discussed in tandem with world birth rate. As the birth rate increases, the production of waste also increases. Decision making models in landfills area that consider positive and negative evaluation give a new dimension for the proposed model of this research. For the first part of the research, ranking of current operating landfill site among the three landfills in Kedah, Malaysia are identified based on intuitionistic fuzzy sets (IFS) in multi-criteria decision making (MCDM).